University Students’ Use of Artificial Intelligence in Academic Work: Efficiency, Learning Quality, and Academic Integrity - Dedi Irwan (Lembaga Riset Ilmiah, 2025)
The rapid integration of artificial intelligence (AI), particularly generative AI tools, has reshaped academic practices in higher education, raising concerns regarding learning quality, academic effort, and ethical conduct. While AI offers significant efficiency gains, its implications for student engagement and integrity remain contested. This study examines university students’ patterns of AI use, their orientation toward efficiency and learning quality, perceptions of academic effort, ethical considerations, and attitudes toward institutional regulation in AI-mediated academic contexts. Using a quantitative cross-sectional survey design, data were collected from 316 undergraduate students across multiple universities and study programs. Responses were gathered through a self-administered online questionnaire consisting of 10 Likert-type items (four- to six-point scales) and analysed using descriptive and correlational statistics in SPSS. The findings reveal that AI use among students is nearly universal, indicating its normalization as an academic resource. Students predominantly employ AI to improve efficiency and accelerate task completion, with efficiency-oriented use more strongly endorsed than learning-oriented use. At the same time, students acknowledge that AI use may reduce academic effort, highlighting a tension between productivity gains and meaningful learning engagement. Ethical concerns are recognised, and perceptions of potential misuse are evident. Importantly, students demonstrate openness toward institutional regulation and AI-aware assessment practices, suggesting a regulation-ready rather than resistant stance. These findings highlight the need for pedagogical and policy approaches that balance efficiency, learning quality, and academic integrity in AI integration. Integrasi cepat artificial intelligence (AI), terutama AI generatif, telah mengubah praktik akademik di pendidikan tinggi dan memunculkan kekhawatiran tentang kualitas pembelajaran, upaya akademik, dan integritas. Meskipun AI menawarkan efisiensi, implikasinya terhadap keterlibatan belajar dan perilaku etis masih diperdebatkan. Penelitian ini mengkaji pola penggunaan AI oleh mahasiswa, orientasi terhadap efisiensi dan kualitas belajar, persepsi mengenai upaya akademik, pertimbangan etis, serta sikap terhadap regulasi institusional. Menggunakan survei kuantitatif potong lintang, data dikumpulkan dari 316 mahasiswa sarjana dari berbagai universitas dan program studi. Data diperoleh melalui kuesioner daring dengan 10 butir skala Likert dan dianalisis menggunakan statistik deskriptif dan korelasional. Hasil menunjukkan bahwa penggunaan AI hampir universal, menandakan normalisasi AI sebagai sumber akademik. Penggunaan berorientasi efisiensi lebih dominan dibanding penggunaan berorientasi pembelajaran. Mahasiswa mengakui bahwa penggunaan AI dapat menurunkan upaya akademik, menciptakan ketegangan antara efisiensi dan keterlibatan belajar yang bermakna. Kekhawatiran etis teridentifikasi dan persepsi potensi penyalahgunaan terlihat. Mahasiswa juga menunjukkan keterbukaan terhadap regulasi institusional dan penilaian yang melek-AI, mencerminkan sikap siap-regulasi dibanding penolakan. Temuan ini menegaskan perlunya desain kebijakan dan pedagogi yang menyeimbangkan efisiensi, kualitas belajar, dan integritas akademik dalam integrasi AI.